Safety and efficacy of minimally invasive percutaneous nephrolithotomy for infantile nephrolithiasis. Single centre experience from Pakistan - Ahmad, Tariq; Minallah, Nasrum; Khaliq, Nida; Rashid, Hania; Syed, Misbah; Almuradi, Moath Ahmad Abdullah (Frontiers in Pediatrics, 2023)
Objective To assess the efficacy and safety of mini-percutaneous nephrolithotomy (PCNL) for small renal stones 1–2 cm in size in infants less than one year. Material and Methods This descriptive case series was conducted in the department of pediatric urology Institute of Kidney Diseases Peshawar, Pakistan, from March 2019 to March 2022. All the patients underwent mini-PCNL in prone position under GA with 14 Fr access sheath and 10 Fr nephroscope. Stone clearance was assessed by non-contrast CT KUB at 30th postoperative day. Patients with no residual fragments on the non-contrast CT KUB were defined as stone-free. Patients with residual fragments of any size were defined as procedure failure. Safety was determined in terms of intra and postoperative complications. Results A total of 51 infants were included in the study. The mean age of patients was 9.6 + 1.8 (5–12 month). The mean stone size was 15.8 + 2.7 (10–21) mm in length and 12.3 + 2.2 (8–17) mm in width. PCNL mean operative time was 51.6 ± 7.1 (40–70) minutes. Complete stone clearance at one month was observed in 46 (90.2%) patients. Residual fragments were seen in 5(9.8%) patients with a mean size of 1.6 + 0.4 (0.9–2.0) mm. None of the patients required any additional procedure for clearance of stones. In 7 (13.7%) patients, some post-operative complications were observe, all were grade I complications, including fever in 5(9.8%) and transient hematuria in 2(3.9%) patients. Conclusion Mini-PCNL is a safe and effective treatment for renal stones in infants measuring 1–2 cm with high SFR and an acceptable complication rate.